2015
DOI: 10.1007/s00467-015-3044-3
|View full text |Cite
|
Sign up to set email alerts
|

Sleep fragmentation and periodic limb movements in children with monosymptomatic nocturnal enuresis and polyuria

Abstract: We found that PLMS and cortical arousals in sleep were increased in children with monosymptomatic NE and polyuria, without a significant association with the enuretic parameters. These observations suggest the presence of a comorbid mechanism driven by a common, independent pacemaker. We hypothesize the autonomic system, its sympathetic branch, and the dopaminergic system as candidates for this pacemaker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 34 publications
1
34
1
Order By: Relevance
“…Our research group confirmed sleep fragmentation in children with refractory nocturnal enuresis by increased cortical arousals using video-polysomnography [9]. Moreover, the increased cortical arousals were associated with increased periodic limb movements during sleep (PLMS) [9,10]. The specific role of PLMS remains unclear.…”
Section: Nocturnal Enuresissupporting
confidence: 55%
“…Our research group confirmed sleep fragmentation in children with refractory nocturnal enuresis by increased cortical arousals using video-polysomnography [9]. Moreover, the increased cortical arousals were associated with increased periodic limb movements during sleep (PLMS) [9,10]. The specific role of PLMS remains unclear.…”
Section: Nocturnal Enuresissupporting
confidence: 55%
“…Sleep disorders [6][7][8][9][10][11] have been described in only a handful of paediatric studies of children with CKD. These were This work has been presented in abstract form at the Canadian Respiratory Conference 2014 and at the American Academy of Sleep Medicine 2014 Conference.…”
Section: Introductionmentioning
confidence: 99%
“…Dhondt et al studied 67 normal children with NE and 67 as a control for PLMS. Children with NE were found to have higher incidence of periodic limb movement and sleep fragmentation [96]. An increased occurrence of night waking and enuresis was observed in children with SCA [24].…”
Section: Periodic Limb Movement Syndrome (Plms) and Restless Leg Syndmentioning
confidence: 95%
“…High rates of SDB and night waking was reported in children with SCA [159]. Sleep fragmentation is a common features in children with SCA and PLMS and RLS [93,96]. Thus repeated cortical arousal might be common in SCA and NE .…”
Section: Cortical Arousal and Ne In Scamentioning
confidence: 98%